Formulasi Sediaan Spray Gel Ekstrak Etanol Pegagan (Centella asiatica (L.) Urban ) Dan Uji Daya Tabir Surya - Rosiana Rizal; Salman; Vadilah Maharani (Jurnal Sains Farmasi Dan Kesehatan, 2023)
Skin damage is caused by sunlight which interferes with the health of human skin, so it needs sunscreen protection, where sunscreen has the ability to protect the skin. Pegagan is a plant that contains many secondary metabolites, one of which is flavonoids which can be used as sunscreen. The research was conducted to formulate a spray gel preparation of pegagan (Centella asiatica (L.) Urban) ethanol extract which has an SPF value for UV radiation protection. Pegagan was extracted by maceration method using 70% ethanol as solvent. The extracts obtained were made into spray gel preparations with concentrations of pegagan ethanol extract F1(2%), F2(4%), and F3(6%). Spray gel from pegagan ethanol extract was evaluated for 28 days including organoleptic, homogeneity, viscosity, pH, adhesive dispersion, and spraying pattern. Determination of the results of sunscreen power using uv-vis spectrophotometry method. The results showed that all of the spray gel preparations had met the requirements. The preparation of pegagan ethanol extract spray gel has a slightly thick texture, dark green color, has a characteristic aroma of pegagan and is homogeneous. It has a viscosity value of 1650,75 cPs-1804,5 cPs, with a pH value of 5,7. The results of the evaluation of the spreadability of sticking to the skin while the spraying pattern is elongated and spread. The activity of sunscreen spray gel ethanol extract of pegagan was measured at a wavelength of 290-320 nm with an interval of 5, the best SPF value was found in formula 3 (6%) with an SPF value of 18,32 including the ultra category.